The Magic Silver Cooking Pot - Gomez, Aduke (Nigeria, 2022)
The Magic Silver Pot could be the perfect solution to Chief Obo's worries about feeding the guests at his daughter's wedding. But it seems the pot has been broken. What is going to happen to the wedding feast now?...
Keywords: Fantasy; Juvenile Fiction